Synthesis and Spectral studies of Benzothiazolo-(2,3-c)-5- Chloro-2,3-Dihydro-1,2,4-Triazepine - Kuberkar, S.V. (Asian Journal of Chemistry, 2010)
2-Hydrazinobenzothiazole (I), on treatment with acrylonitrile, gave β-(2-hydrazinobenzothiazolyl)-propiononitrile (II) which was hydrolysed to corresponding acid (III). The corresponding acid chloride, on heating in the presence of pyridine, gave benzothiazolo-(2,3-c)-2,3-dihydro-1,2,4-triazepin-5-one (IV). This seven-membered keto product on treatment with phosphoryl chloride gave benzothiazolo-(2,3-c)-5-chloro-2,3-dihydro- 1,2,4-triazepine (V) which was also obtained directly by heating β-(2-hydrazinobenzothiazolyl)-propanoic acid (III) with phosphoryl chloride. Structures of the compounds have been established by elemental analysis and spectral data.